PENDIDIKAN ADVOKASI DALAM MENCIPTAKAN SUMBER DAYA MANUSIA SIAP BEKERJA - Nurdzaki Arifin Fadhillah (CV. ADIBA AISHA AMIRA, 2024)
Advocacy education has become a primary focus in preparing human resources ready to face the challenges of the complex work environment. This article discusses the crucial role of advocacy education in shaping individuals who not only possess strong technical knowledge but also the advocacy skills necessary for success in various professional contexts. Advocacy education helps students understand their rights and responsibilities, hones communication, negotiation, and conflict resolution skills, as well as fosters ethical attitudes in decision-making. Through holistic advocacy education, human resources can be equipped with the skills needed to become influential and innovative leaders in the workplace. This research outlines the importance of integrating advocacy education into formal and non- formal education curricula to create learning environments supportive of the development of competitive human resources in the era of globalization.